1982
DOI: 10.1080/15287398209530188
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term oral toxicity of 2,4,6‐trinitrotoluene in mice, rats, and dogs

Abstract: The short-term oral toxicity of 2,4,6-trinitrotoluene (alpha-TNT) was determined in dogs, rats, and mice. Single-dose oral LD50s for alpha-TNT in corn oil were 1320 and 794 mg/kg in male and female rats, respectively, and 660 mg/kg in both male and female mice. For multiple-dose studies, dogs were dosed daily for up to 13 wk with alpha-TNT at 0, 0.2, 2.0, or 20 mg/kg by capsule; rats received 0, 0.002, 0.01, 0.05, or 0.25% and mice received 0, 0.001, 0.005, 0.025, or 0.125% alpha-TNT in their diets over the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 3 publications
6
71
0
Order By: Relevance
“…The calculated log Kow value of 2.03 (Liu et al 1983a (Opresko 1995a). In the first study, Dilley et al (1982) administered TNT to dogs, rats, and mice for 13 wk. Groups of 2 male and 2 female beagle dogs were administered doses of 0, 0.2, 2.0, or 20 mglkg/d in gelatin capsules.…”
Section: Metabolism and Bioconcentrationmentioning
confidence: 99%
“…The calculated log Kow value of 2.03 (Liu et al 1983a (Opresko 1995a). In the first study, Dilley et al (1982) administered TNT to dogs, rats, and mice for 13 wk. Groups of 2 male and 2 female beagle dogs were administered doses of 0, 0.2, 2.0, or 20 mglkg/d in gelatin capsules.…”
Section: Metabolism and Bioconcentrationmentioning
confidence: 99%
“…Studies on mice, rats, and dogs have demonstrated that TNT exposure may result in a variety of adverse health effects including cardiovascular, gastrointestinal, hematological, hepatic, renal, immunological, neurological, reproductive, developmental, genotoxic, and carcinogenetic effects [186]. Recent mammalian studies conducted on mice and rats [222,223] administered up to 601 mg TNT per kg body weight to whitefooted mice over a 14-day period. While fatalities were not observed [222], several indicators of nonspecific immunity, including increased spleen weight, were related to dose.…”
Section: Vertebratesmentioning
confidence: 99%
“…Recent mammalian studies conducted on mice and rats [222,223] administered up to 601 mg TNT per kg body weight to whitefooted mice over a 14-day period. While fatalities were not observed [222], several indicators of nonspecific immunity, including increased spleen weight, were related to dose. Results of dosing studies with hispid cotton rats suggest that hepatic enzymes and hemolytic anemia may be useful biomarkers of terrestrial contamination by explosives [223].…”
Section: Vertebratesmentioning
confidence: 99%
“…The presence of these compounds in the sediments and soils from munitions facilities has been demonstrated at concentrations high enough to adversely affect some algal, vascular plant, invertebrate, and fish species (6,28). Toxic effects of 2,4,6-trinitrotoluene (TNT) exposure on mammals have been investigated (9,21,22); however, information specific to amphibian exposures is lacking. Yet, TNT and metabolites have been shown to bioaccumulate in terrestrial salamanders in a soil matrix (19).…”
Section: Introductionmentioning
confidence: 99%